Hands-On Data Structures and Algorithms with JavaScript : Write efficient code that is highly performant, scalable, and easily testable using JavaScript. - Mukkamala, Kashyap (Packt Publishing, 2018)
Data structures and algorithms are the fundamental building blocks of computer programming. They are critical to any problem, provide a complete solution, and act like reusable code. Using appropriate data structures and having a good understanding of algorithm analysis are key in JavaScript to solving crises and ensuring your application is ...
Keywords: JavaScript.; Data structures.; Web programming.; Programming & scripting languages: general.; Internet: general works.; Computers -- Programming Languages -- JavaScript.; Computers -- Web -- Site Design.; Computers -- Web -- General.